On the minimizers of the fusion frame potential - Heineken, Sigrid Bettina (2018)
We study the minimizers of the fusion frame potential in the case that both the weights and the dimensions of the subspaces are fixed and not necessarily equal. Using a concept of irregularity we provide a description of the local (that are also global) minimizers which projections are eigenoperators of the fusion frame operator. This result will be related to the existence of tight fusion frames. In this way we generalize results known for the classical vector frame potential.